Using Reforestation Rules for the Purposes of Environmental Cost Accounting in Forest Fire Investigations - N. V. Mikhaleva; S. G. Golubeva (Теория и практика судебной экспертизы, 2017)
The paper examines the possibilities of using forestry regulations, including the Rules of Reforestation adopted on June 29, 2016 by Decree No. 375 of the Ministry of Natural Resources andEnvironment of the Russian Federation, for the assessment of remediation costs by environmental forensic scientists